Analisis Postur Tubuh Menggunakan Metode RULA, REBA Pada Pekerja di Divisi Packaging - Ade Rizky Sya'bana; Dene Herwanto (Jurnal Serambi Engineering, 2023)
In the process of moving cement products from the packaging department to several trucks, human power is required. Workers who transfer finished cement products from belt conveyors to trucks take a long time to lift heavy workpieces which can cause disturbances in the limbs as a result of repetitive work. Therefore, an analysis is needed that aims to determine the level of safety of work postures as a basis for improving the work posture of workers. In analyzing body posture, the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods are used. The results of the study found that the analysis of worker posture using the RULA method was 7, this indicates that the job requires investigation and changes to SOP. Based on the REBA score of 6, it indicates that the work has a moderate risk level, with an action level of 2 and further action for evaluation of the work system needs to be carried out. Changes to the work system are made in order to minimize the risk of musculoskeletal complaints in workers so that it will affect the level of worker productivity.